A bibliometric analysis of publications on burn sepsis using VOSviewer - Cao, Zhi; Zhang, Yu; Luo, Jin-Hua; Liao, Wen-Qiang; Cheng, Xing; Zhan, Jian-Hua (Frontiers in Medicine, 2022)
Background: Sepsis is one of the most common complications in burn patients and causes high morbidity, especially in those with severe burns. Nevertheless, there are no formal criteria for diagnosing and treating burn sepsis. Therefore, the bibliometric analysis will be applied to reveal research trends in this field and predict its possible hot spots. Methods: We screened for relevant literature on burn sepsis that met the inclusion criteria of the Web of Sciences (WOS) database and analyzed publication trends and research hot spots in related fields using VOSviewer software. Results: From 1981 to 2022, we screened 2486 documents that met the requirements and analyzed them bibliometrically. The American scholar Herndon DN had a much higher h-index (47) than other authors. Most published, cited, and h-indexed publications are from the USA (Np: 1193, Nc: 42154, H: 98). The second most publishing country is China, but the second most cited and h-indexed country is Germany. Burns also outperforms other journals in this field (Np: 376, Nc: 8019, H: 46). “Biomarkers” is a newly emerging keyword (cluster “clinical research,” APY was 2018.16), and clinically relevant research in burn sepsis maybe a future research trend. Conclusions: Sepsis in burn patients has unique pathophysiological characteristics, and the general diagnostic criteria for sepsis lack specificity. Therefore, we must establish a database and construct an intelligent predictive model to help achieve a more individualized and precise early diagnosis and treatment of burn sepsis. This may also be an important development direction for future research in this field.